PENGARUH KEDISIPLINAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PENGAWAS CLEANING SERVICE PT ARSA MANAJEMEN FASILITAS ZONA METRO JAKARTA - Yesinta Putri Inggar Pananti; Rian Sri Rahayu (Al Hasanah Barokah Foundation, 2026)
This study aims to determine the Influence of Work Discipline and Work Environment on the Performance of Cleaning Service Supervisors at PT ARSA Manajemen Fasilitas Zona Metro Jakarta both partially and simultaneously. This type of research uses a descriptive quantitative method. The sampling technique uses a saturated sample of 60 respondents. The correlation coefficient value of 0.804 means that it has a very strong relationship level and the determination coefficient value of 64.6% means that supervisor performance is influenced by work discipline 64.6%. This is evidenced by the hypothesis test obtained a calculated t value> t table (4.178> 2.002) and is strengthened by a significant value <0.05 (0.000 <0.05). The correlation coefficient value of 0.816 means that it has a very strong relationship level and a determination coefficient of 66.6% means that supervisor performance is influenced by the work environment by 66.6%. This is proven by the hypothesis test obtained tcount> ttable (4.698> 2.002) and is strengthened by a significant value <0.05 (0.000 <0.05). The correlation value of 0.863 means that it has a very strong relationship level and a determination coefficient of 74.5% means that supervisor performance is influenced by work discipline and work environment by 74.5% while the remaining 25.5% is influenced by other factors. This is proven by the hypothesis test obtained the value of F count > F table (83.111 > 3,16) and strengthened by the significant value < 0.05 (000 < 0.05). Thus it is proven that H0 is rejected and Ha is accepted.